Integrasi Pendekatan Deep Learning dalam Pembelajaran IPAS SD dan Dampaknya terhadap Hasil Belajar - Fathurrahman Akbar; Harlina Ramelan (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Elementary school science and social studies (IPAS) learning is currently still dominated by conventional, rote-oriented methods (teacher-centered), resulting in shallow conceptual understanding and relatively low student learning outcomes. This study aims to describe the integration of the deep learning approach in IPAS learning at elementary schools and to comprehensively analyze its impact on student learning outcomes. The research method used is a Systematic Literature Review (SLR) applying the PRISMA protocol through the Sinta-accredited national journal database within the last five years of publication. Based on the synthesis of the included articles, it was found that the integration of deep and interactive learning approaches significantly exerts a multidimensional positive impact on students' learning profiles. This innovative instructional tactic is proven to boost classical completeness in the cognitive domain through long-term conceptual retention, optimize affective responses in the form of motivation and curiosity through a joyful learning environment, and sharpen process skills in children's psychomotor domain collaboratively. The implication of this study demands a reform of educators' instructional designs to shift toward interactive media and contextual problem-solving models to support the success of the Merdeka Curriculum.